2003
DOI: 10.2139/ssrn.356302
|View full text |Cite
|
Sign up to set email alerts
|

Price Indices for Information and Communication Technology Industries - An Application to the German PC Market

Abstract: Changing product quality, rapid technological progress, and short product life cycles make it difficult to compute indices that correctly reflect the true price movements of IT products. This paper assesses the differences between traditional and quality adjusted indices by providing results for PC hardware. Transaction price data for the period from 1985 to 1994 are used to construct price indices for personal computers in Germany.The use of hedonic methods allows to correct for quality changes. Quality-adjus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The second way was proposed by Daveri (2001); he assumed that the PPP property in weak form holds, so the rate of change of the IT assets prices in Greece must be equal to the rate of change in the IT assets prices in the United States plus the devaluation rate of the US dollar with respect to the Greek Drachma/ Euro. Moch (2001) found that quality-adjusted prices of German PCs decline at the same pace with the prices of US PCs, if we control for differences in exchange rates. We use both methods together with the official price index.…”
Section: Appendix B Hedonic Price Indexmentioning
confidence: 86%
“…The second way was proposed by Daveri (2001); he assumed that the PPP property in weak form holds, so the rate of change of the IT assets prices in Greece must be equal to the rate of change in the IT assets prices in the United States plus the devaluation rate of the US dollar with respect to the Greek Drachma/ Euro. Moch (2001) found that quality-adjusted prices of German PCs decline at the same pace with the prices of US PCs, if we control for differences in exchange rates. We use both methods together with the official price index.…”
Section: Appendix B Hedonic Price Indexmentioning
confidence: 86%
“…We also tested a model where the inefficiency term is not fixed over time, so that we get time- 1984, 19931986, 19991986, 19941986, 199719961997Maxima 1985, 20011983, 1993, 20021991, 20011985, 1994, 20011981, 20021985, 1991, 2001 * Estimated by using a Cobb-Douglas-production function with Harrod-neutral technological progress. ** Cf.…”
Section: Technology Efficiency Effects Frontiersmentioning
confidence: 99%
“…Unfortunately, hedonic price deflators for OCM investment or the output of the OCM industry do not exist for Germany (Deutsche Bundesbank 2000). For personal computers, some work is carried out by Moch (2001). He estimates quality-adjusted price indices for personal computers for the period 1985 to 1994 and finds that the prices of personal computers adjusted for exchange rate movements are declining as fast as in the U.S.. To deflate nominal investment, we employ the U.S. Bureau of Economic Analysis's (BEA's) price index for OCAM equipment adjusted for exchange rates movements, which partly uses hedonic techniques to correct for quality change.…”
Section: Data and Descriptive Statisticsmentioning
confidence: 99%